Ethnic Chinese in Contemporary Indonesia (Book collections on Project MUSE., 2008)
The Chinese in Indonesia have played an important role in Indonesian society before and after the fall of Soeharto. This book provides comprehensive and up-to-date information by examining them in detail during that era with special reference to the post-Soeharto period. The contributors to this volume consist of both older- and younger-generation scholars writing on Indonesian Chinese. They offer new information and fresh perspectives on the issues of government policies, legal position, ethnic politics, race relations, religion, education and prospects of the Chinese Indonesians.